A traveller and the road : the journey of an Indian communist - Sen, Mohit (New Delhi : Rupa & Co., 2003)
Autobiography of an Indian communist.
Includes index.
Keywords: Sen, Mohit; Communists -- India -- Biography; Communism -- India -- History